Early Christian prayer and identity formation - Hvalvik, Reidar; Sandnes, Karl Olav (Wissenschaftliche Untersuchungen zum Neuen Testament, 2014)
Early Christian prayer and identity formation : introducing the project /Reidar Hvalvik and Karl Olav Sandnes --Identity and prayer /Mikael Tellbe --The place of Jesus in earliest Christian prayer and its import for early Christian identity /Larry Hurtado --Praying with outstretched hands : nonverbal aspects of early Christian prayer and the question of identity /Reidar Hvalvik --Prayer, 'othering' and the construction of early Christian identity in the Gospels of Matthew and Luke /Geir Otto Holmås --Prayer and social identity formation in the Letter to the Ephesians /Mikael Tellbe --Prayer in Acts and the Pastoral Epistles : intersections of gender and class /Anna Rebecca Solevåg --With our eyes fixed on Jesus : the prayers of Jesus and his followers in Hebrews /Ole Jacob Filtvedt --Heavenly prayer and Christian identity in the Book of Revelation /Craig R. Koester --"The First Prayer" : Pater Noster in the early church /Karl Olav Sandnes --The Lord's Prayer and the eucharist prayers in the Didache /Hans Kvalbein --"What point is there for me in other people hearing my confessions?" : prayer and Christian identity in Augustine's Confessions /Reidar Aasgaard --Christians praying in a Graeco-Egyptian context : intimations of Christian identity in Greek papyrus prayers /Anastasia Maravela --Prayer in the Valentinian Apolytrosis : a case study on Gnostic identity /Niclas Förster --"Bring now, O Zeus, what difficulty thou wilt." : prayer and identity formation in the Stoic philosopher Epictetus /Glenn Wehus --Prayer and identity formation : attempts at a synthesis /Reidar Hvalvik and Karl Olav Sandnes.